Contemporary research findings on dentine remineralization. (16th August 2013) - Zhong, Bo; Peng, Ce; Wang, Guanhong; Tian, Lili; Cai, Qiang; Cui, Fuzhai
Abstract: Dentine remineralization is important for the treatment of dentine caries and the bonding durability of dentine and resin materials in clinical practice. Early studies of dentine remineralization were mostly based on the classical pathway of crystallization, which involves large‐scale deposition of calcium phosphate crystals on collagen and is achieved in a liquid environment containing mineral ions. Results from these studies were unsatisfactory and not suitable for clinical application because they did not simulate the ordering of hydroxyapatite in the collagen fibres of natural teeth. As studies on collagen type I and non‐collagenous proteins have advanced, dentine biomimetic remineralization has become a popular research topic and has shifted to processes involving intrafibrillar remineralization, which is more similar to natural tooth formation. The objective of this review was to summarize current theory and research progress as it relates to dentine remineralization. Copyright © 2013 John Wiley & Sons, Ltd.